A Model on Generation of Profit and the Role of Money- A System Dynamics Approach - Mohammed, Munir; Patra, Soumendra Ku. (Prabandhan: Indian Journal of Management, 2010)
Once upon a time, money was supposed to be the only medium of exchange. But now, we see it is not only the medium of exchange, but the basis of production and also the intriguing basis for creating the profit. It is the general belief of the people that a business will exist if there is a profit and it vanishes if the business incurs losses. The profit is made in the business, if the selling price is more than the cost, but the business incurs a loss if the selling price is less than the cost and there is a breakeven point when the total cost equals the total sales and there is no profit and no loss.